Mediating Role of Organisational Strategies in Relationship of the Causes and Out-Comes of Occupational Stress - Ahmad, Tehseen; Qureshi, Qamar Afaq (International Journal of Psychosocial Rehabilitation, 2020)
Everyone has the right to spend his life happily. But the question arises “HOW. The goal of this research paper is to identify the Mediating role of Organizational strategies in the relationship of causes (Individual stressors, Group stressors, organizational stressors, & Extra-organizational stressors) and outcomes (Depression, Absenteeism, & Trauma, etc.) of occupational stress. The researcher has applied the qualitative tools of thematic analysis like “argumentation” to analyses the results of current studies (research paper). For the field study, a questionnaire was used to gather the first-hand view on the topic, using a seven-point interval scale to agree or disagree with the statements to analysis the empirical relationships. Two hundred and fifty-two judges and advocates represented by 18 females and 234 males completed a constructed and standardized questionnaire. The empirical results from the currents study tell that mediating variable, i.e. organizational strategies play a very significant role while reducing the level of stress among the employees.